Calcium Lactate Pentahydrate Crystallization in the Presence of Pentanoic Acid. Issue 6 (3rd May 2018) - Kiran-Yildirim, Bercem; Titiz-Sargut, Sibel; Sayan, Perviz
Abstract: Calcium lactate crystallization was investigated in the presence of pentanoic acid in a mixed‐suspension mixed‐product removal (MSMPR)‐type crystallizer. Filtration rate measurements were carried out to define the effect of pentanoic acid on the filtration characteristics of calcium lactate pentahydrate crystals. The average particle size, length‐to‐width ratio, and morphologies of calcium lactate pentahydrate crystals were also determined and examined as a function of pentanoic acid concentrations. The zeta potential of calcium lactate pentahydrate crystals was measured. Thermogravimetric and differential thermal analysis (TGA‐DTA) as well as X‐ray diffraction (XRD) were performed and Coats and Redfern's method was used to verify the kinetic parameters in the dehydration steps observed in the TGA curves. Abstract : The effect of pentanoic acid on calcium lactate pentahydrate (CLP) crystallization was investigated. The obtained experimental data can serve as a reference to enhance the physical properties of CLP crystals to be used in pharmaceutical industry and to achieve retardation of undesired formation of calcium lactate on cheese surface by promoting the crystal growth to a certain extent.